2019
DOI: 10.5430/afr.v8n3p136
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Level of Compliance of International Accounting Standard IAS 38: Evidence from Bahrain

Abstract: This research aims to examine the level of compliance of International Accounting Standard 38 (IAS 38, intangible assets) among the listed companies of Bahrain Bourse. This paper employs the method of equal weighted disclosure index to determine if the listed firms are complying with the disclosure requirements of the IAS 38. The required data for the year 2016 has been obtained from Bloomberg. The research found that firms have a compliance of 35.4%. The regression analysis results showed that there is a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Some studies came in a line with the theory and provided evidence that the leverage has positive association with level of IFRS compliance (Al-Shammari et al, 2008;Samaha & Stapleton, 2009). Another study reported correlation between these leverage and compliance with IFRS (Hassan et al, 2019). On the other hand, (Kumar & Saini, 2016); and Sarea and Abdulla (2015) found negative significant association while Tsegba et al 2017reported negative but not significant association.…”
Section: Level Of Compliance With Ifrs 16 and Company Leveragementioning
confidence: 84%
See 4 more Smart Citations
“…Some studies came in a line with the theory and provided evidence that the leverage has positive association with level of IFRS compliance (Al-Shammari et al, 2008;Samaha & Stapleton, 2009). Another study reported correlation between these leverage and compliance with IFRS (Hassan et al, 2019). On the other hand, (Kumar & Saini, 2016); and Sarea and Abdulla (2015) found negative significant association while Tsegba et al 2017reported negative but not significant association.…”
Section: Level Of Compliance With Ifrs 16 and Company Leveragementioning
confidence: 84%
“…They found that the level of compliance differed by industry type and the investment sector has highest while the insurance industry has the lowest. In other study, Hassan et al (2019) studied the level of compliance of IAS 38 by companies listed on Bahrain stock market for the year 2016. They found that the level of compliance is 35.4% and the audit firm size, profitability, leverage and industry type are correlated with it, while age and company size is not.…”
Section: Scientific Journal For Financial and Commercial Studies And mentioning
confidence: 99%
See 3 more Smart Citations